Good Governance Principles in Waste Management in the Greater Bandung Region, West Java Province, Indonesia - Rochmansjah, Heru (International Journal of Science and Society, 2024)
The waste problem is a public issue because it concerns the interests of the wider community, so it requires optimal management and compliance with the principles of good governance. This study examines the problem of implementing good governance principles in waste management in Greater Bandung area which includes Bandung City, Bandung Regency, West Bandung Regency and Cimahi City. It is known that these four regions jointly use Sarimukti TPA as an integrated waste processing site. The results of the study show that the principles of good governance have not been fully implemented in Greater Bandung waste management. At least four of the nine good governance principles have not been fulfilled, namely participation, rule of law, transparency and consensus orientation. Because it concerns public needs, waste management in Greater Bandung must also involve non-government parties so that cooperation takes place on the three pillars of good governance, namely government-private-community. This collaboration can be carried out through a collaborative governance model which ensures that stakeholders from outside the government are directly involved, both in the preparation and determination, also the implementation process of waste management policies.